Analisis Pengaruh Kapur Tohor dan Kaustik Soda Terhadap Kenaikan pH Air Limbah Tambang di Settling Pond 1 Pada Stockpile PT Nantoy Bara Lestari Desa Pandreh Kecamatan Teweh Tengah Kabupaten Barito Utara Kalimantan Tengah - Malau, Andri Antonius; Fidayanti, Neny; Putrawiyanta, I Putu; Sukmawatie, Neny; Indrajaya, Fahrul (Universitas Pahlawan Tuanku Tambusai, 2025)
Coal mine wastewater typically has acidic characteristics that can pose environmental hazards if not properly treated. This study aims to evaluate the effectiveness of quicklime (CaO) and caustic soda (NaOH) in increasing the pH level of mining wastewater at Settling Pond 1, PT Nantoy Bara Lestari, located in Pandreh Village, Teweh Tengah District, Central Kalimantan. The research employed a jar test method using various dosages applied to 1 liter of water samples. The results indicated that the initial pH of the wastewater was 2.85, significantly below the regulatory standard (6–9). After treatment, both reagents successfully increased the pH of the wastewater, with optimal doses at 0.7 g/L for quicklime and 0.2 g/L for caustic soda. However, caustic soda demonstrated greater effectiveness at lower doses compared to quicklime. These findings suggest that caustic soda may serve as a more efficient alternative for active treatment of mining wastewater. This study is expected to contribute as a reference for pH-based wastewater management in mining operations. Keywords: mining wastewater, pH, quicklime, caustic soda, settling pond